Molecular phylogeny of Atractocarpus (Rubiaceae): taxonomic implications for several New Caledonian Gardenieae species - Mouly, Arnaud; Barrabé, Laure; Bruy, David (Plant ecology and evolution, 2021)
Background and aims - New Caledonia is a hotspot of biodiversity in the world. Among the most diverse New Caledonian plant families is Rubiaceae, which consist of 30 genera containing 220 species, with a level of endemism of 93%. The tribe Gardenieae is represented by four genera, Gardenia (8 species), Aidia (2 species), Randia (7 species), and Atractocarpus (10 species). As Randia has now been restricted to the Neotropics, the New Caledonian Randia species remain unplaced within the tribe. Atractocarpus is a Pacific genus, easily characterized by long imbricated stipules, a feature also present in the Randia species and in several Gardenia species in New Caledonia. The aims of the present study are to test the monophyly of Atractocarpus and to assess the phylogenetic placement of the Randia and Gardenia species with long imbricated stipules within Gardenieae and specifically their relationships with taxa of the Porterandia group to which Atractocarpus belongs. Material and methods - We investigated 63 species of Pacific Gardenieae, with a focus on the Porterandia group, in a Bayesian phylogenetic reconstruction (cpDNA: trnTF and rpl32, and nrDNA: ITS). Key results - Our study provides a mostly supported consensus tree topology of the Porterandia group. Five Gardenia and seven Randia species fall within a clade that comprises the New Caledonian Atractocarpus species, rendering both Atractocarpus and Gardenia polyphyletic. Conclusion - We enlarge the delimitation of Atractocarpus to include 12 New Caledonian Randia and Gardenia species. New Caledonia is consequently confirmed as the centre of diversity for Atractocarpus with 31 species. According to our study, three genera of Gardenieae occur in the archipelago: Aidia, Gardenia, and Atractocarpus .